Soybean-inspired nanomaterial-based broadband piezoelectric energy harvester with local bistability. (1st December 2022) - Hao, Fengqian; Wang, Biao; Wang, Xu; Tang, Tao; Li, Yimeng; Yang, Zhengbao; Lu, Jian
Abstract: Bistable nonlinear energy harvesters are effective structures for scavenging broadband energy from frequency-varying vibration sources. The bistable characteristic of such structures is typically induced by introducing magnetic fields, prestress, and nonuniform geometries or fixtures. However, the complicated structures or single deformation modes of these structures limit their practical application. Inspired by the structure of soybean pods, a bionic metallic nanomaterial-based bistable piezoelectric energy harvester is developed in this study. The nanoplate substrate with a local bistable region mimics the configuration of a soybean pod. To the best of the authors' knowledge, the local bistable configuration represents a novel energy harvesting strategy. The local bistable nanoplate is fabricated using a mature surface mechanical attrition treatment technique that generates a gradient nanostructure to enhance the mechanical properties of the bistable structure. The energy harvesting performance and nonlinear dynamic characteristics of the energy harvester are evaluated through frequency-sweep and fixed-frequency vibration tests and numerical simulations with a new two-step finite element (FE) model. The harvester characteristics in three vibration modes (single-well vibration (SV), intermittent cross-well vibration (ICV), and continuous cross-well vibration (CCV)) are discussed. The experimental and numerical results demonstrate that the voltage output and working bandwidth of the proposed harvester increase by five times in the ICV and CCV modes when the excitation acceleration increases from 0.5 g to 3.0 g . The bionic nanomaterial-based bistable piezoelectric energy harvester can be potentially used in various applications such as vehicle suspension systems, tires, and vehicle-bridge systems. Graphical Abstract: ga1 Highlights: Soybean pod-mimic nanoplate-based broadband bistable piezoelectric energy harvester for vibration energy harvesting. Nanoplate with a local bistable region processed by a facile method of surface mechanical attrition treatment (SMAT). Novel two-step FE model for analyzing local bistable/multistable problems. Three vibration modes including single-well vibration, continuous cross-well vibration, and intermittent cross-well vibration. 500% improvement in working bandwidth and voltage output generated by nonlinear cross-well vibrations of the bionic harvester.